2020
DOI: 10.1364/oe.383781
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-narrowband polarization insensitive transmission filter using a coupled dielectric-metal metasurface

Abstract: A coupled dielectric-metal metasurface (CDMM) consisting of amorphous silicon (a-Si) rings and subwavelength holes in Au layer separated by a SiO 2 layer is presented. The design parameters of the CDMM is numerically optimized to have a polarization independent peak transmittance of 0.55 at 1540 nm with a Full Width at Half Maximum (FW H M) of 10 nm. The filter also has a 100 nm quite zone with ∼ 10 −2 transmittance. A radiating two-oscillator model reveals the fundamental resonances in the filter which interf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Therefore, it is often difficult to eliminate the detuning between the two coupled F-W BIC and low-Q resonance in singlelayer MMs. For double-layer MMs, not only can the two resonances be independently designed, but the near-field coupling of them can also be effectively manipulated by adjusting the relative displacement or distance of the two structures [42][43][44][45], which provides the possibility for the realization of an ideal BIC-based EIT. However, there is no research work reported on this issue yet.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is often difficult to eliminate the detuning between the two coupled F-W BIC and low-Q resonance in singlelayer MMs. For double-layer MMs, not only can the two resonances be independently designed, but the near-field coupling of them can also be effectively manipulated by adjusting the relative displacement or distance of the two structures [42][43][44][45], which provides the possibility for the realization of an ideal BIC-based EIT. However, there is no research work reported on this issue yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, the realization of the typical atomic EIT effect requires some harsh working conditions including ultra-low temperature and high intensity pumping, which prevents its on-chip integration. To overcome the listed drawbacks, various classical systems have been demonstrated to mimic the EIT effect, such as electric circuits [6], plasmonic structures [7], microcavity [8], photonic crystal waveguides [9] and metamaterials (MTMs) [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to that, the unusual properties, such as the inversion of Snell's law [1], negative refractive index [2,3] and electromagnetic (EM)-wave absorption [4,5], are obtained easily. Therefore, the MM is promising for the potential applications such as sensors [6][7][8], superlens [9,10], filters [11,12], antennas [13,14], and so on.…”
Section: Introductionmentioning
confidence: 99%